K–12 School Counselors Utilizing Critical Race Theory to Support the Racial Identity Development and Academic Achievement of African American Males. Issue 1 (January 2021) - Appling, Brandee; Robinson, Shanel
This article examines the role of racial identity development in the academic achievement of African American adolescent males. Through the lens of critical race theory (CRT), we highlight how K–12 school counselors may support and enhance the schooling experiences of African American males by understanding and acknowledging how racial identity development may impact academic achievement. A focus on CRT in education emphasizes the continual persistence of racism ingrained in K–12 education located within the educational opportunities, curriculum, representation, and teacher perception of African American males. We offer insight into how school counselors may work to decrease barriers to achievement by analyzing the effect race and gender have on the identification, retention, and underachievement of their African American male students.